Endovascular skills guidewire and catheter skills for endovascular surgery - Schneider, Peter A. (Informa Healthcare, 2009)
Endovascular Skills has been the go-to guide for training in minimally invasive vascular surgery for the last four years, and now is completely updated and revised. Well-organized progression of topics mirrors the clinician's own progression of skill advancement, in an easy-to-read text, supported by clear, simplistic line drawings, which make for a well-illustrated practical guide for the seasoned and novice practitioner alike.